Integralidade, intersetorialidade e promoção da saúde em ações de cuidado à saúde de escolares: encaminhamentos em outros países e na macrorregião oeste do Paraná – Brasil - Bordin, Vanessa (2022)
The study aims to analyze health activities for schoolchildren in different countries and in the Western Paraná macro-region, based on the principle of integrality, intersectoriality and health promotion. For that, an exploratory, descriptive study was developed, based on documentary sources and a quantitative approach with health professionals. The documentary research was carried out from the study of nine countries, including Brazil whose data were accessed through the pages available on the internet and the quantitative data were obtained through a questionnaire with closed questions, self-administered, to be completed online. Documentary data show that working at school and developing programmatic actions in all countries has been growing; actions are aimed at creating habits for the future life of students and their families, highlighting nutritional care; childhood obesity prevention; promotion of body practices, physical activity and leisure; prevention of problematic use and abuse of alcohol, tobacco, crack and other psychoactive substances; mental health; sexual and reproductive rights and prevention and control of Sexually Transmitted Infections. Fiftynine health professionals participated in the qualitative research, of which 30 participated in the 2017-2018 cycle of the PSE and 26 in the 2021-2022 cycle. The quantitative data related to the PSE in Brazil were systematized in tables and distributed in absolute and relative frequencies, showing that the majority of the participants are nurses and, among the actions carried out, those to combat the Aedes aegypti mosquito, verification and updating of vaccination status and promotion of healthy eating and prevention of childhood obesity with higher participation rates for the two studied cycles. As for the training actions, these were mentioned as being carried out occasionally, rarely or never, in addition to the difficulty of intersectoral articulation and high turnover of managers. Monitoring is carried out by E-SUS; joining the PSE aims to access the resources provided for in the program; actions are carried out jointly by the education and health service; detected problems are attended to at the health unit or referred to specialized services, but not always easily; participants consider their participation in the PSE to be good or fair. It is seen that intersectoriality, integrality and health promotion are challenges in the local reality and in the experiences studied in other countries.